Thickness effects on the magnetism of Ho thin films - Herring, A; Nuttall, W; Thomas, M; Goff, J; Stunault, A; Ward, R; Wells, MR; Stirling, W (2005)
This study was undertaken to probe any thickness dependence of the magnetic ordering in Ho film samples of thickness 1000 monolayers (ML), 100 ML and 50 ML. The study was carried out on the antiferromagnetic helical magnetic phase in the temperature range 65 → 132 K (TN). The magnetism was studied by x-ray magnetic scattering using the resonant process at the Ho L III absorption edge, 8.071 keV. It was found that the magnetic modulation wavevector, τ, of the Ho helical structure changed systematically with temperature over the range 65 K → TN. No evidence of a change in τ with changing layer thickness was seen. The value of the Néel temperature TN decreased from 130 K for the 1000 ML sample to 110 K for the 50 ML sample. The critical exponent β of the transition between the helical to paramagnetic state is measured as β ≈ 0.5 for the 1000 and 100 ML samples compared to a literature value of β = 0.39 for bulk. For the 50 ML film, β = 0.28 ± 0.05. The measured values of β are discussed in terms of strain and reduced dimensionality. © 2005 IOP Publishing Ltd.